Seismic Response on Thin Shell as Structural Foundation - Min, Yee Hooi; Azizah, Abdul Nassir; Kim, Jae Yeol (Korean Association for Spatial Structures, 2024)
This study aims to investigate the seismic response of a large span thin shell structures and assess their displacement under seismic loads. The study employs finite element analysis to model a thin shell structure subjected to seismic excitation. The analysis includes eigenvalue analysis and time history analysis to evaluate the natural frequencies and displacement response of the structure under seismic loads. The findings show that the seismic response of the large span thin shell structure is highly dependent on the frequency content of the seismic excitation. The eigenvalue analysis reveals that the tenth mode of vibration of the structure corresponds to a large-span mode. The time history analysis further demonstrates, with 5% damping, that the displacement response of the structure at the critical node number 4920 increases with increasing seismic intensity, reaching a maximum displacement of 49.87mm at 3.615 seconds. Nevertheless, the maximum displacement is well below the allowable limit of the thin shell. The results of this study provide insight into the behaviour of complex large span thin shell structures as elevated foundations for buildings under seismic excitation, based on the displacement contours on different modes of eigenvalues. The findings suggest that the displacement response of the structure is significant for this new application of thin shell, and it is recommended to enhance the critical displacement area in the next design phase to align with the findings of this study to resist the seismic impact.